Exploring Bias in Pre-Trained CNNs: Fairness Assessment in Sjögren’s Disease Detection - Santos, Bruna Ferreira dos; Berton, Lilian (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
Sjögren’s disease is an autoimmune disorder that primarily affects moisture-producing glands, leading to symptoms such as dry eyes, dry mouth, and systemic complications. Accurate diagnosis remains a challenge, particularly in medical imaging applications. In this study, we employ various Convolutional Neural Networks (CNNs) for Sjögren’s disease detection, using a dataset with inherent biases. The goal is to analyze the impact of transfer learning on fairness, investigating whether pre-trained models amplify or mitigate biases in medical image classification. We compare different CNN architectures and evaluate fairness metrics to assess performance disparities across demographic subgroups. The findings contribute to the development of bias-aware AI models, ensuring more equitable and reliable deep learning applications in health.